Translation Procedures of Harsh Language and Their Correlation to the Visual in The Life and Times of Scrooge McDuck - Janis Ramadhanti Saputri; Andika Wijaya (Journal of Language and Literature, 2022)
Comics are media that people of all ages can enjoy, and while some comics have age restriction, The Life and Times of Scrooge McDuck is a comic that targets both young and old readers. As it is the story of Scrooge McDuck’s rise to success, the comic depicts aggressiveness not only physically through violence and facial expression but also verbally through the usage of harsh language. The objective of this research is to analyze (1) the translation procedures that are used in the comic The Life and Times of Scrooge McDuck and (2) their correlation with the visual elements of the comic. This research uses Vinay and Darbelnet (1958/1998) theories on translation procedures by basing the utterance of harsh language on theories proposed by Ljung (2011) and Ford (2016). This research uses the qualitative descriptive method, and the data were taken by setting the limitation on the character’s facial expression at the time of the utterance of harsh language. From this research, it can be concluded that the translator utilizes many translation procedures to translate the harsh language, in particular the reduction procedure. This research also shows that translation procedures are utilized to reduce the element of verbal aggressiveness, yet the procedures that are used do not influence the intention behind the utterance as the aggressiveness has been presented through the visuals.